A study of biochemical parameters of composted and fresh municipal wastes - García, Carlos Andrés; Hernández, Teresa; Costa, Costas; Ceccanti, Brunello; Masciandaro, Grazia; Ciardi, Carlo (My University, 1993)
Three different groups of municipal organic materials (fresh city refuse, sewage sludge and the composted products of both) were characterized from a biochemical point of view, and ATP content and 5 hydrolase activities (total and extractable) determined. The highest ATP values were found in the sludges and the lowest in the composts demonstrating that this parameter is valid for following the degradation of organic matter in this kind of waste. The highest total urease activities were found in sewage sludges, while activities varied widely in the solid municipal wastes, suggesting the existence of some kind of inhibitor. Protease-BAA activity was low in all cases. The highest phosphatase and β-glucosidase activity occurred in the sewage sludges. With the exception of protease-casein, all the enzymes studied were positively correlated with ATP content. Protease-casein, β-glucosidase and phosphatase activities were correlated among themselves and with the different fractions of carbon contained in the wastes. As regards extracellular enzymes, only phosphatase was correlated with the carbon content of the Na4P2O7 extract. Extracellular protease-BAA activity was generally very low. Extracellular urease activity was higher in city refuse than in sewage sludge, while phosphatase activity was higher in the latter. All enzymatic activities decreased with composting.
Keywords: Municipal solid wastes; Sewage sludge; Composts; ATP; Urease; Proteases; β-glucosidase; Phosphatase; Organic matter; Extracellular hydrolases